The little Italian hotel [large type] - Patrick, Phaedra (Wheeler Publishing, a part of Gale, a Cengage Company, 2023)
"Ginny Splinter, acclaimed radio host and advice expert, is sure her husband, Adrian, will love the special trip to Italy she's planned for their twenty-fifth wedding anniversary. But when Ginny presents the gift to Adrian, he surprises her with his own very different plan--a divorce. Beside herself with heartache, Ginny impulsively invites four heartbroken listeners to join her in Italy while live on air. From hiking the hills of Bologna to riding a gondola in Venice, Ginny and her newfound company embark on a vacation of healing. However, when Adrian starts to rethink their relationship, Ginny must decide whether to commit to her marriage or start afresh, alone"--